2004
DOI: 10.1046/j.1572-0241.2003.04002.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Cholecystectomy for Acute Calculous Cholecystitis: A Meta-Analysis

Abstract: Early operation (open or laparoscopic) does not carry a higher risk of mortality and morbidity compared to delayed operation and should be the preferred surgical approach for patients with acute lithiasic cholecystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
152
1
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(169 citation statements)
references
References 35 publications
4
152
1
12
Order By: Relevance
“…Several studies have shown that performing LC within 72 h of presentation does not increase morbidity and mortality [6,9] . Early LC, furthermore, has been shown to have a lower complication rate, decreased length of stay, decreased cost, and a shorter post-operative recovery period compared to delayed LC [5,7,8,16,17] . The results from a meta-analysis by Papi et al of 12 prospective randomized trials from 1970-2000 (9 addressing open cholecystectomy, 3 addressing LC), showed that there was a decrease in conversion to open procedure when LC was done early (17.6% vs 25.7%) and there were fewer post-operative complications (10.9% vs 15.6%) [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that performing LC within 72 h of presentation does not increase morbidity and mortality [6,9] . Early LC, furthermore, has been shown to have a lower complication rate, decreased length of stay, decreased cost, and a shorter post-operative recovery period compared to delayed LC [5,7,8,16,17] . The results from a meta-analysis by Papi et al of 12 prospective randomized trials from 1970-2000 (9 addressing open cholecystectomy, 3 addressing LC), showed that there was a decrease in conversion to open procedure when LC was done early (17.6% vs 25.7%) and there were fewer post-operative complications (10.9% vs 15.6%) [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies too have reported the similar finding ELC being better than DLC. [16][17][18][19] As is evidenced above, most of the studies depict that ELC is better DLC for outcomes such as mortality, morbidity, cost and length of stay. Some studies have even discussed the rare complications that may occur surgically or post operatively.…”
Section: Early Versus Delayed Cholecystectomymentioning
confidence: 99%
“…cholecystectomy for acute cholecystitis by the experienced surgeons. 5,6,7,8,9 Our study was designed to analyse and compare the results of lap. cholecystectomy in patients with features of acute cholecystitis.…”
Section: Introductionmentioning
confidence: 99%